1993
DOI: 10.1126/science.8385367
|View full text |Cite
|
Sign up to set email alerts
|

Phosphatidylinositol 3-Kinase Encoded by Yeast VPS 34 Gene Essential for Protein Sorting

Abstract: The VPS34 gene product (Vps34p) is required for protein sorting to the lysosome-like vacuole of the yeast Saccharomyces cerevisiae. Vps34p shares significant sequence similarity with the catalytic subunit of bovine phosphatidylinositol (PI) 3-kinase [the 110-kilodalton (p110) subunit of PI 3-kinase], which is known to interact with activated cell surface receptor tyrosine kinases. Yeast strains deleted for the VPS34 gene or carrying vps34 point mutations lacked detectable PI 3-kinase activity and exhibited sev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
740
3
10

Year Published

1997
1997
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 906 publications
(764 citation statements)
references
References 32 publications
11
740
3
10
Order By: Relevance
“…Full length ATR, together with a mutant sequence which results in the introduction of the alteration D2494E in the kinase domain (Schu et al, 1993), were cloned into the mammalian expression vector pEBG-2T, which contains a GST tag (Sanchez et al, 1994). HEK293 cells were transfected by a calcium phosphate-mediated protocol and extracts subjected to glutathione-agarose puri®cation (see Materials and methods).…”
Section: Expression Of Atr In Hek293 Cells and Isolation By Glutathiomentioning
confidence: 99%
“…Full length ATR, together with a mutant sequence which results in the introduction of the alteration D2494E in the kinase domain (Schu et al, 1993), were cloned into the mammalian expression vector pEBG-2T, which contains a GST tag (Sanchez et al, 1994). HEK293 cells were transfected by a calcium phosphate-mediated protocol and extracts subjected to glutathione-agarose puri®cation (see Materials and methods).…”
Section: Expression Of Atr In Hek293 Cells and Isolation By Glutathiomentioning
confidence: 99%
“…The yeast homologue of the p110 catalytic subunit of the mammalian PtdIns 3-kinase, VPS34p, is a lipid kinase with substrate specificity towards PtdIns. It cannot form PtdIns3,4P 2 or PtdIns3,4,5P 3 , and VPS34 mutants are disturbed in membrane flow (Schu et al, 1993;Stack & Emr, 1994). Therefore, the important factor here seems to be PtdIns3P, since the two other lipid molecules are absent in yeast cells.…”
Section: Autophagy and Signal Transductionmentioning
confidence: 99%
“…An important advance in the study of protein sorting was the discovery that phosphatidylinositol 3-kinase (PI 3-kinase), which phosphorylates phosphatidylinositol to phosphatidylinositol 3-phosphate (PtdIns3P), is required for the transport of membrane proteins to the yeast vacuole [11]. Subsequent work with intact mammalian cells showed that pharmacologic inhibition of PI 3-kinase by the drugs LY294002 or wortmannin inhibits the intracellular trafficking of receptors, including the recycling of transferrin receptors [12][13][14][15] and the degradation of PDGF receptors [16,17].…”
Section: Introductionmentioning
confidence: 99%